Evaluation of Natural Zeolite and Bentonite as Catalysts in Cyclohexanone Oxidation with Hydrogen Peroxide - Muhammad Hidayatullah; Sahrul Wibiyan; Risfidian Mohadi; Aldes Lesbani (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2025)
The catalytic oxidation of cyclohexanone using environmentally benign oxidants remains a key challenge in sustainable organic synthesis. In this study, natural zeolite (clinoptilolite and mordenite) and bentonite were evaluated as heterogeneous catalysts for the oxidation of cyclohexanone with hydrogen peroxide under reflux at 90 °C. Structural characterization by X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) confirmed the aluminosilicate frameworks, where clinoptilolite exhibited the highest crystallinity, followed by bentonite and mordenite. The oxidation products were analyzed using FTIR, melting point measurements, and gas chromatography–mass spectrometry (GC–MS). Despite the catalytic activity of all materials, FTIR and melting point analyses revealed that the expected adipic acid was not formed under the applied conditions. GC–MS results indicated the formation of partially oxidized oxygenated intermediates such as alcohols, ethers, and carbonyl derivatives, whose distribution strongly depended on the catalyst’s pore structure and surface properties. Clinoptilolite promoted confined partial oxidation due to its microporous structure, whereas bentonite facilitated non-selective oxidation owing to its open layered framework. These findings emphasize that the interplay between molecular confinement and oxygen accessibility governs the selectivity of cyclohexanone oxidation and provides insights for the rational design of improved zeolite- and clay-based catalytic systems for green oxidation reactions.